2020
DOI: 10.1111/mcn.13071
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diets matter for children's dietary quality: Seasonal dietary diversity and animal‐source foods consumption in rural Timor‐Leste

Abstract: Improving the dietary quality of women and children is essential to reduce all forms of malnutrition. In this study, we assessed seasonal child and maternal dietary diversity and consumption of animal‐source foods (ASF), using 1,236 observations from combined data collected among 167 mother–child dyads in rural Timor‐Leste. We used generalized linear and logistic mixed‐effects models to examine the dietary differentials of mothers and children in two agricultural livelihood zones and across the seasons, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
3
21
1
Order By: Relevance
“…In a case-control study in Dhaka, Bangladesh 42 % ( 22 ) also has higher findings than the present study. But this finding is higher than from studies done in Leseto14⋅4 % ( 23 ) and Ghana 17⋅2 % ( 11 ) . This difference might be due to sampling size, study design, setting, climate, tradition, poverty status and nutrition intervention.…”
Section: Discussioncontrasting
confidence: 55%
“…In a case-control study in Dhaka, Bangladesh 42 % ( 22 ) also has higher findings than the present study. But this finding is higher than from studies done in Leseto14⋅4 % ( 23 ) and Ghana 17⋅2 % ( 11 ) . This difference might be due to sampling size, study design, setting, climate, tradition, poverty status and nutrition intervention.…”
Section: Discussioncontrasting
confidence: 55%
“…A recent comprehensive review of seasonal determinants of undernutrition in South Asia identified just 1 study, from 1985, exploring seasonality of dietary intakes among infants in Bangladesh, which predated development of the MDD indicator ( 15 , 16 ). A recent study conducted among 6- to 59-mo-old children and their mothers from Timor-Leste found evidence of lower dietary diversity during the dry and wet seasons compared with the dry and transition seasons, although a lower threshold of only 2 food groups was used to define low dietary diversity compared with the MDD indicator ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of seasonality of the FGS and certain components (i.e., specific food groups) could be explained in part by a buffering effect, as different items in a food group become available across different seasons. For example, provitamin A–rich orange fruits, such as mangoes, often have widespread availability during a very limited season in many countries ( 30 , 34 ). In some cultures, fruits are also perceived to be more of a child's food, which could strengthen seasonal patterns of consumption in this age group ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal dietary quality and education, more so than agroecological characteristics, are the factors that explain the diet of children. A study by Bonis-Profumo et al 4 highlighted that addressing the dietary quality of children in Timor-Leste benefitted from improving women's diets through better access to nutritious foods and secondary education. The dietary intake of mothers is a strong predictor of children's dietary quality achievements.…”
Section: Introductionmentioning
confidence: 99%
“…The mean food group intake of women and children aged 24 to 59 months were almost identical, suggesting that when foods are consumed by mothers, these are also given to older children. 4 A poor dietary intake is associated with adverse health outcomes for the mother (such as increased risk of preeclampsia and gestational diabetes, and excessive gestational weight gain), adverse birth outcomes (such as premature birth and low birth weight), and adverse health outcomes in childhood and adult life (such as increased risk of developing chronic diseases like diabetes or coronary heart disease). [5][6][7] Many dietary factors have been associated with newborns small for gestational age, such as quality and unhealthy patterns, [8][9][10] high sugar consumption during pregnancy, 11 low consumption of seafood, 12,13 low iodine intake, 14 and caffeine consumption.…”
Section: Introductionmentioning
confidence: 99%